Defense Mechanisms and Repressive Coping Among Male Breast Cancer Patients - Weber, Rainer; Ehrenthal, Johannes C.; Brock-Midding, Evamarie; Halbach, Sarah; Würstlein, Rachel; Kowalski, Christoph; Ernstmann, Nicole (Frontiers in Psychiatry, 2021)
Objectives: The concept of defense mechanisms has undergone extensive revision and expansion since Freud first described these processes. Initially formulated as an unconscious repression of unpleasant memories, with further development focusing on the role of defense mechanisms in the regulation of internal conflicts, the concept shifted and evolved to incorporate the adaptation to external demands, including intrapsychic and interpersonal handling of burden of illness. In addition to defense mechanisms, coping provides another perspective on human adjustment to difficult life events. While there is substantial research on both coping and defense mechanisms in various psychiatric and somatic diseases, including cancer, little is known about defensive regulation, coping, and their interaction in male breast cancer patients. Methods: The present study is part of the N-Male project conducted between 2016 and 2018 in Germany (Male breast cancer: patients' needs in prevention, diagnosis, treatment, rehabilitation, and follow-up care). Semi-standardized interviews with 27 male breast cancer patients were analyzed with regard to defense mechanisms. In addition, fear of progression and repressive coping was assessed by self-report. Results: There was considerable variety in levels of defensive functioning as well as repressive coping in our sample. We found no difference in overall levels of defensive functioning between men with vs. without repressive coping. However, patients with repressive coping demonstrated a decopupled association between fear of progression and defensive functioning as compared to patients without repressive coping. Discussion: The study provides the first evidence of disease processing in male breast cancer patients Knowledge of patients' defense patterns and repressive coping seems promising for better planning targeted intervention strategies.